Proteomic analysis of serum in workers exposed to diesel engine exhaust. (28th December 2021) - Rahman, Mohammad L.; Bassig, Bryan A.; Dai, Yufei; Hu, Wei; Wong, Jason Y. Y.; Blechter, Batel; Hosgood, H. Dean; Ren, Danzhi; Duan, Huawei; Niu, Yong; Xu, Jun; Fu, Wei; et al.
Abstract: Diesel engine exhaust (DEE) is classified as a Group 1 human carcinogen. Using a targeted proteomics approach, we aimed to identify proteins associated with DEE and characterize these markers to understand the mechanisms of DEE‐induced carcinogenicity. In this cross‐sectional molecular epidemiology study, we measured elemental carbon (EC) using a personal air monitor and quantified 1317 targeted proteins in the serum using the SOMAScan assay (SOMALogic) among 19 diesel exposed factory workers and 19 unexposed controls. We used linear regressions to identify proteins associated with DEE and examined their exposure‐response relationship across levels of EC using linear trend tests. We further examined pathway enrichment of DEE‐related proteins using MetaCore. Occupational exposure to DEE was associated with altered levels of 22 serum proteins (permutation p < .01). Of these, 13 proteins (CXCL11, HAPLN1, FLT4, CD40LG, PES1, IGHE.IGK..IGL, TNFSF9, PGD, NAGK, CCL25, CCL4L1, PDXK, and PLA2G1B) showed an exposure‐response relationship with EC ( p trend < .01), with serum levels of all but PLA2G1B declining with increasing air levels of EC. For instance, C‐X‐C Motif Chemokine Ligand 11 (CXCL11) showed the most significant association with DEE ( β = −0.25; permutation p = .00004), where mean serum levels were 4121.1, 2356.7, and 2298.8 relative fluorescent units among the unexposed, lower exposed (median, range : 56.9, 40.2–62.1 μg/m 3 EC), and higher exposed (median, range of EC: 72.9, 66.9–107.7 μg/m 3 EC) groups, respectively ( p trend = .0005). Pathway analysis suggested that these proteins are enriched in pathways related to inflammation and immune regulation. Our study suggests that DEE exposure is associated with altered serum proteins, which play a role in inflammation and immune regulation.